Construction and Engineering Application of an Anti-Disturbance Control Power Supply System for Key Auxiliary Equipment in Coal-Fired Power Plants Under Weak Grid Conditions - Zhao Hancheng (Pelopor Publikasi Akademika, 2026)
In response to the frequent occurrence of grid disturbances such as voltage sags caused by the weak grid structure in the area where the Datang Jinguang Kalteng Power Plant in Indonesia is located, which have led to power-loss trips of key auxiliary equipment including the coal feeder control system and motor-operated valves (MOVs), posing a serious threat to the safe and stable operation of the generating units, this study carries out applied research and engineering retrofitting of an anti-grid-disturbance control power supply system. Through systematic analysis of historical grid disturbance characteristics and the tolerance capabilities of coal feeder control equipment, a high-reliability control power upgrade solution based on online double-conversion UPS and an intelligent power distribution system is designed and implemented, establishing a